Electronic fiscal device (EFD's): A tool of enhancement of value added tax (VAT) compliance in Tanzania : A case of Tanzania Revenue Authority(TRA) -Arusha region - Leonard, David (Mzumbe University, 2024)
A dissertation submitted in partial fulfillment of the requirements for award of the Degree of Master of Business Administration – Corporate Management (MBA-CM) of Mzumbe University